Neurobrucellosis Presenting with Unilateral Abducens Nerve Palsy - ANDISHEH, Mohsen; AMIRSALARI, Susan; TORKAMAN, Mohammad; SABZECHIAN, Marzieh; AFSHARPAIMAN, Shahla (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Andisheh M, Amirsalari S, Torkaman M, Sabzechian M, Afsharpaiman Sh. Neurobrucellosis Presenting with Unilateral Abducens Nerve Palsy. Iran J Child Neurol. Spring 2017; 11(2):61-64. Abstract One of the rare complications of brucellosis is neurobrucellosis. There have been numerous reports showing clinical forms of brucellosis affecting CNS, such as cranial nerve involvement, myelitis, vascular disease, radiculoneuritis, meningitis, meningoencephalitis, and demyelinating disease. In this case report, we introduce a 2.5 yr old girl with unilateral abducens nerve palsy referred to Baghiyatallah Hospital Outpatient Clinic, Tehran, Iran in June 2015. References 1. Pappas G, Akritidis N, Bosilkovski M, Tsianos E. Brucellosis. N Engl J Med 2005; 352:2325–2336. 2. Al-Sous MW, Bohlega S, Al-Kawi MZ, Alwatban J, McLean DR. Neurobrucellosis: clinical and neuroimaging correlation. AJNR Am J Neuroradiol 2004; 25:395–401 3.Bingöl A, TogayIsikay C. Neurobrucellosis as an exceptional cause of transient ischemic attacks. Eur J Neurol 2006; 13:544–548. 4.Adaletli I, Albayram S, Gurses B, et al. Vasculopathic changes in the cerebral arterial system with neurobrucellosis. Am J Neuroradiol 2006; 27:384–386. 5.Shakir RA, Al-Din AS, Araj GF, Lulu AR, Mousa AR, Saadah MA. Clinical categories of neurobrucellosis. A report on 19 cases. Brain 1987; 110:213–223. 6.Esra Özkavukcu, Zeynep Tuncay, Ferda Selçuk, İlhan Erden: An unusual case of neurobrucellosis presenting with unilateral abducens nerve palsy: clinical and MRI findings; Turkish Society of Radiology 2009 7. Tena D, Gonzáles-Praetorius A, LópezAlonso A, Peña JL, Pérez-Pomata MT, Bisquert J. Acute meningitis due to Brucella spp. Eur J Pediatr 2006; 165:726–727. 8. Rangel Guerra R, Martinez HR, Leon Flores L. Neurobrucellosis. Report of five cases and literature review. Rev Inwest Clin 1982;34:62–8. 9. Mugerwa RD, D’Arbela PG. Brucella meningitis; a case report and review of the literature. East African Med J 1976;53:266–9. 10. Bashir R, Al-Kawi MZ, Harder EJ, Jinkins J. Nervous system brucellosis: diagnosis and treatment. Neurology 1985; 35:1576–1581. 11. Al Deeb SM, Yaqub BA, Sharif HS, Phadge JG. Neurobrucellosis: clinical characteristics, diagnosis, and outcome. Neurology 1989; 39:498–501. 12. Lubani MM, Dudin KI, Araj GF, Manandhar DS, Rashid FY. Neurobrucellosis in children. Pediatr Infect Dis J 1989;8:79–82. 13. Santini C, Baiocchi P, Berardelli A, Venditti M, Serra P. A case of brain abscess due to Brucella melitensis. Clin Infect Dis 1994;19:977–8. 14. Koussa S, Chemaly R. Neurobrucellosis presenting with diffuse cerebral white matter lesions. Eur Neurol 2003; 50:121–123. 15. Fincham RW, Sahs AL, Joynt RJ. Protean manifestation of nervous system brucellosis. Case histories and a wide variety of clinical forms. JAMA 1963; 184:269–275 16. Marconi G. Su un caso di sclerosis multipla acuta insorta dopo un’infezione da Brucella abortus. Riv Patol Nerv Ment 1966; 87:548–565. 17. Bussone G, La Mantia L, Grazzi L, Lamperti E, Salmaggi A, Strada L. Neurobrucellosis mimicking multiple sclerosis: a case report. Eur Neurol 1989; 29:238–240. 18. KarakurumGöksel B, Yerdelen D, Karataş M, et al. Abducens nerve palsy and optic neuritis as initial manifestation in brucellosis. Scand J Infect Dis 2006; 38:721–725. 19. Yilmaz M, Ozaras R, Mert A, Ozturk R, Tabak F. Abducent nerve palsy during treatment of brucellosis. Clin Neurol Neurosurg 2003; 105:218–220.